Deskripsi Penerapan Model Experiential Learning dalam Pembelajaran Matematika ditinjau dari Kecerdasan Emosional Siswa - Zurachmad, Sitti Muslimah; Arsyad, Nurdin; Dassa, Awi (Issues in Mathematics Education (IMED), 2024)
The aim of this research to describe the implementation of experiential learning model in the perspective of students’ emotional intelligence at class VIII 10 at Junior High School. This is descriptive research employing a qualitative approach. Research subjects were 2 students, 1 student with a high level of emotional intelligence and 1 student with a low level of emotional intelligence. The instruments used in this study consist of the students’ self-evaluation sheet, the students’ response questionnaire, the student emotional intelligence questionnaire, the mathematics learning outcomes test, and the interview question test. Data collection techniques used in this research consist of mathematics test, questionnaire, and interview. The experiential learning model has 4 stages, namely, concrete experience, reflective observation, abstract conceptualization, and active experimentation. The result of this research showed that: (1) Students’ activities in the implementation of the experiential learning model were conducted well. The students had been involved actively so the teacher’s domination in learning lessened. Students with a high and low level of emotional intelligence were able to follow each stage of the learning model. (2) The student with a high level of emotional intelligence has a very good response to the implementation of experiential learning model, and the student with a low level of emotional intelligence gave also a very good response. (3) Students’ mathematics learning outcomes as a result of the implementation of experiential learning model achieved the classroom completeness level of 85%.